Biomimetic Materials and Fabrication Approaches for Bone Tissue Engineering. Issue 23 (24th November 2017) - Kim, Hwan D.; Amirthalingam, Sivashanmugam; Kim, Seunghyun L.; Lee, Seunghun S.; Rangasamy, Jayakumar; Hwang, Nathaniel S.
Abstract: Various strategies have been explored to overcome critically sized bone defects via bone tissue engineering approaches that incorporate biomimetic scaffolds. Biomimetic scaffolds may provide a novel platform for phenotypically stable tissue formation and stem cell differentiation. In recent years, osteoinductive and inorganic biomimetic scaffold materials have been optimized to offer an osteo‐friendly microenvironment for the osteogenic commitment of stem cells. Furthermore, scaffold structures with a microarchitecture design similar to native bone tissue are necessary for successful bone tissue regeneration. For this reason, various methods for fabricating 3D porous structures have been developed. Innovative techniques, such as 3D printing methods, are currently being utilized for optimal host stem cell infiltration, vascularization, nutrient transfer, and stem cell differentiation. In this progress report, biomimetic materials and fabrication approaches that are currently being utilized for biomimetic scaffold design are reviewed. Abstract : Biomimetic scaffolds may provide a platform for phenotypically stable tissue formation and stem cell differentiation for bone tissue engineering. For this reason, various methods for engineering 2 or 3D structures have been developed. In this Progress Report, the biomimetic materials and fabrication approaches that are currently being utilized for biomimetic bone scaffold design are discussed.